Controlled fusion frames - Musazadeh, K.; Khosravi, A. (Methods of Functional Analysis and Topology, 2012)
We use two appropriate bounded invertible operators to define a controlled fusion frame with optimal fusion frame bounds to improve the numerical efficiency of iterative algorithms for inverting the fusion frame operator. We show that controlled fusion frames as a generalization of fusion frames give a generalized way to obtain numerical advantage in the sense of preconditioning to check the fusion frame condition. Also, we consider locally controlled frames for each locally space to obtain new globally controlled frames for our Hilbert space. We develop some well known results in fusion frames to the controlled fusion frames case.